A study on searchable encryption schemes - Buchade, Sunitha; Devale, P.R. (International Journal of Engineering and Technology, 2018)
To manage large volume of data, most of the organizations and data owners outsource their data to remote cloud storage servers. Since the remote servers are untrusted party, the data has to be encrypted to achieve security and privacy. But encryption and decryption causes communication overhead for many data utilization operations like searching and updating. To overcome this contradiction, searchable encryption notion was introduced. Searchable encryption (SE) is an ability of a server to search upon the ciphertext and retrieve the data without decrypting it. By searching on the ciphertext it protects the user’s tactful data. This article concentrates on study of various resil-ient keyword search schemes in area of Cloud SE. The main basis for SE evolution is attaining the challenging task of efficient enci-phered data utilization with privacy check. Thus schemes are developed considering their search capability, efficiency and security. In this paper we summarize and analyze various available keyword searchable schemes based on query expressiveness and query correct-ness. We review articles which have extensively researched in the field of SE with various keyword search schemes.